Distinct Immunological Landscapes Characterize Inherited and Sporadic Mismatch Repair Deficient Endometrial Cancer - Ramchander, Neal C.; Ryan, Neil A. J.; Walker, Thomas D. J.; Harries, Lauren; Bolton, James; Bosse, Tjalling; Evans, D. G.; Crosbie, Emma J. (Frontiers in Immunology, 2020)
Around 30% of endometrial cancers (EC) are mismatch repair (MMR) deficient, mostly as a consequence of mutations acquired during tumorigenesis, but a significant minority is caused by Lynch syndrome (LS). This inherited cancer predisposition syndrome primes an anti-cancer immune response, even in healthy carriers. We sought to explore the intra-tumoral immunological differences between genetically confirmed LS-associated MMR-deficient (MMRd), sporadic MMR-deficient, and MMR-proficient (MMRp) EC. Endometrial tumors from women with known LS were identified (n=25). Comparator tumors were recruited prospectively and underwent microsatellite instability (MSI) testing, immunohistochemistry (IHC) for MMR expression and MLH1 methylation testing. Those found to have MLH1 hypermethylation formed the sporadic MMR-deficient group (n=33). Those found to be mismatch repair proficient and microsatellite stable formed the MMR-proficient group (n=35). A fully automated monoplex IHC panel was performed on sequential formalin-fixed paraffin-embedded tumor sections to identify CD3+, CD8+, CD45RO+, FoxP3+, and PD-1+ immune cells, and PD-L1 expression by tumor/immune cells. Two independent observers quantified immune marker expression at the tumor center and invasive margin. Mean and overall compartmental T-cell counts generated standard (binary: Low/High) and higher resolution (quaternary: 0-25%, 25-50%, 50-75%, 75-100%) immune scores, which were used as explanatory features in neural network, support vector machine, and discriminant predictive modeling. Overall T-cell counts were significantly different between the three cohorts: CD3+ (p=<0.0001), CD8+ (p=<0.0001), CD45RO+ (<0.0001), FoxP3+ (p=<0.0001) and PD1+ (p=<0.0001), with LS-associated MMR-deficient tumors having highest infiltrations. There were significant differences in CD8+ (p=0.02), CD45RO+ (p=0.007) and PD-1+ (p=0.005) T-cell counts at the invasive margin between LS-associated and sporadic MMR-deficient tumors, but not between sporadic MMR-deficient and MMR-proficient tumors. Predictive modeling could accurately determine MMR status based on CD8+ T-cell counts within the tumor center alone. This study shows that LS-associated and sporadic MMR-deficient EC are distinct immunological entities, which has important implications for treatment and prognosis.